Scarcity amidst plenty: Regulating digital transformation - Arewa, Olufunmilayo B. (Frontiers in Research Metrics and Analytics, 2022)
Digital transformation has become a core aspect of lived experiences in recent years. Digital transformation has led to many aggregate benefits in the United States and throughout the world. The distribution of these benefits remains an issue of continuing contention. Digital transformation has occurred in contexts of significant disruption, both positive and negative. Although the positive aspects of disruption are often celebrated, potential negative consequences of digital transformation may not be adequately recognized. Digital transformation may, along with other factors, intensify existing societal divides, lead to greater inequality in many places, and contribute to a scarcity of opportunity for many people. Dealing with potentially adverse consequences of digital transformation requires flexible approaches to regulation and systematic use of metrics. Digital transformation also implicates policy issues, including those concerning technology infrastructure and education and training. Digital economy policies must take account of the requirements of an economy permeated with the effects of digital transformation. Addressing digital economy adversities will require greater attention to digital economy participation and inclusion. Fostering digital economy inclusion requires attention to both the distribution of digital economy benefits and preconditions for digital economy participation.